Distinct raindrop size distribution microphysical mechanisms of frontal and warm-sector heavy rainfall in Coastal Southeast China - Mingrui Guo; Wen Lin; Jingjing Lv; Chenglong Gong; Qing Duan; Jingxi Sun; Pengcheng Lin; Chunsong Lu; Yiqi Chen (Atmospheric Research, 2026)

Arginine and putrescine ameliorate heat stress-induced testicular inflammation and apoptosis via inhibiting endoplasmic reticulum stress in mice - Kun Wu; Chenglong Yu; Guangmang Liu; Yong Zhuo; Bin Feng; Lianqiang Che; Shengyu Xu; Lun Hua; Jian Li; Zhengfeng Fang; De Wu; Yan Lin (Theriogenology, 2026)

Experimental study of a dual-chain transmission hybrid power generation wave energy converter - Chenglong Li; Guojun Pan; Hui Li; Beichen Lin; Shaohui Yang; Weiwei Fan; Xianbin Yan (Ocean Engineering, 2026)

An on-axis integrated microfluidic chemiluminescence immunoassay platform for rapid multiplex biomarker quantification - Qingjin Wu; Yujian Liu; Hailin Wu; Chenglong Wang; Quandong Li; Yongping Lin; Jiao Yang; Peng Li; Yingchun Li (Chemical Engineering Journal, 2026)

Preparation of a MOF-derived Mn-Ti catalyst and its simultaneous removal of NOx and toluene: Strong metal-support interaction and Lewis acid sites - Yongchao Zhong; Dan He; Qiangwei Lu; Lu Wang; Yunkuo Luo; Dongliang Zhang; Chaochao Li; Lin Li; Fengying Li; Xiang Tu; Chenglong Yu (Journal of Environmental Chemical Engineering, 2026)

Beyond Borders: Tracking Water and Carbon Footprints of Global Transport Modes - Chenglong Wang; Xuewei Guo; Chenyang Shuai; Xi Chen; Wei Huang; Lin Gan; Jingran Sun; Bu Zhao (Water Resources Management, 2026)

Differential impacts of ocean acidification and alkalinization on shell microstructure and molecular responses in Mytilus edulis - Zhaohao Chen; Yubin Hu; Xiaoru Lin; Chenglong Lei; Yuanning Li; Yuan Wang; Chao Li; Zhishuai Qu; Jinzhe Du (Marine Environmental Research, 2026)

Oblique convergence drives left-lateral slip on the Altyn Tagh Fault: Evidence from crustal anisotropy - Chenglong Wu; Tao Xu; Jiyan Lin; Tongtong Xie; Xiaobo Tian; Zhanwu Lu (Science China Earth Sciences, 2026)

Magnetic activated biochar prepared via a novel iron-loading method for efficient lead adsorption and recyclability - Li Chao; Bang Yao; Chenglong Liu; Yang Liu; Chunbao Zhou; Yingwen Zhang; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Jing Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Coconut shell inspired coating for impact-resistant and corrosion-protection of oil and gas pipelines - Zhengyu Liu; Li Zhang; Chenglong Mou; Xueqian Cao; Lin Chen; Guangan Zhang; Qunji Xue (Chemical Engineering Journal, 2025)

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

Simulation of surface water–groundwater interaction in coal mining subsidence areas: A case study of the Kuye River Basin in China - Xiang Li; Song Du; Shihang Hu; Donglin Dong; Dong Jiang; Chenglong Cao; Gang Lin; Jingying Fu (Journal of Hydrology, 2025)

Closing the oceanic lithium budget by continental shelf sediment removal - Qingquan Hong; Guang-Yi Wei; Gaojun Li; Yi-Bo Lin; Feifei Zhang; Shilei Li; Chenglong Wang; Zhimian Cao; Pinghe Cai; Tianyu Chen (Earth and Planetary Science Letters, 2025)

Study on the antioxidant defense of Pacific oysters (Crassostrea gigas) against sulfonamide antibiotics - Hao Chen; Liping You; Jing Sun; Hao Yu; Wei Sun; Changlin Song; Bo Su; Chenglong Ji; Lin Ye; Shujun Li; Yanmin Qi; Yuanqing Ma (Aquaculture, 2025)

Chitosan/oxidized cellulose composite nanofiber sponges: a rapid and effective hemostasis strategy for non-compressible hemorrhage - Zhan Zhang; Zhiyuan Lin; Chenglong Yu; San Ieng Lei; Lu Wang; Fujun Wang; Jing Gao; Wenbo Meng (Carbohydrate Polymers, 2025)

Regulating the Cu-Ce interaction of CuCeOx/SAPO-34 catalysts to achieve a wide reaction temperature window for the collaborative synergistic removal of NOx and toluene at low temperatures and reaction mechanisms - Rong Liu; Xuehui Jia; Lin Li; Fengying Li; Xiang Tu; Weicheng Xu; Hansun Fang; Danping Li; Hong Huang; Chenglong Yu (Journal of Hazardous Materials, 2025)

A century of advances in molecular genetics and breeding for sustainable resistance to rice blast disease - Xilai Huang; Wei Yao; Qianru Chen; Jinjun Lin; Jun Huang; Yuying Zou; Chenglong Guo; Bei He; Xiao Yuan; Chengyang Xu; Xionglun Liu; Yinghui Xiao; et al. (Theoretical and Applied Genetics, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

An Approach to Optimize the Efficiency of an Air Turbine of an Oscillating Water Column Based on Adaptive Model Predictive Control - Yan Huang; Weixun Dong; Jianyu Fan; Shaohui Yang; Zhichang Du; Yongqiang Tu; Chenglong Li; Beichen Lin (Journal of Marine Science and Engineering, 2025)
Wave energy, as a vast renewable resource, remains underutilized despite its high potential. The oscillating water column (OWC) is one of the most efficient way to harvest wave energy. Due to the randomness of ocean wave excitation, a control strategy is needed to keep the conversion efficiency of OWC at a certain level. In this paper, an adaptive model predictive control (AMPC) method is proposed to optimize the efficiency of the air turbine and improve the overall efficiency of the OWC. Experiments were conducted in a wave flume to obtain realistic wave data, which were fed into the AMPC model for simulations. Results indicate that AMPC-optimized turbine efficiency exhibits improved performance under regular wave conditions and significantly enhances efficiency within certain intervals under short-period irregular waves. However, as the wave period increases, optimization becomes less stable. Overall, the study concludes that the adaptive MPC model effectively optimizes turbine efficiency under most conditions, highlighting its potential for enhancing OWC performance.

Deciphering the microbiome, lipopolysaccharides, and metabolome interplay: Unveiling putrescine's mechanism for enhancing sperm quality in heat-stressed boars - Chenglong Yu; Hao Li; Lun Hua; Lianqiang Che; Bin Feng; Zhengfeng Fang; Shengyu Xu; Yong Zhuo; Jian Li; De Wu; Junjie Zhang; Yan Lin (Theriogenology, 2025)

Anti-sediment wear coupled corrosion protective coating for oil and gas exploitation pipeline protection - Zhengyu Liu; Jingzhou Liu; Chenglong Mou; Li Zhang; Xueqian Cao; Lin Chen; Guangan Zhang; Qunji Xue (Chemical Engineering Journal, 2025)

Increased Mineral‐Associated Organic Carbon and Persistent Molecules in Allochthonous Blue Carbon Ecosystems - Yuan Li; Chuancheng Fu; Chenglong Ye; Zhaoliang Song; Yakov Kuzyakov; Tony Vancov; Laodong Guo; Zhongkui Luo; Lukas Van Zwieten; Yidong Wang; Yu Luo; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal wetlands contain very large carbon (C) stocks—termed as blue C—and their management has emerged as a promising nature‐based solution for climate adaptation and mitigation. The interactions among sources, pools, and molecular compositions of soil organic C (SOC) within blue C ecosystems (BCEs) remain elusive. Here, we explore these interactions along an 18,000 km long coastal line of salt marshes, mangroves, and seagrasses in China. We found that mineral‐associated organic C (MAOC) is enriched in BCEs dominated by allochthonous inputs and abundant active minerals, leading to an increased proportion of persistent organic molecules. Specifically, soils with large allochthonous inputs (> 50%) are characterized by a substantial contribution of MAOC (> 70%) to total SOC with a notable preservation of lipids (36%) across salt marshes, mangroves, and seagrasses. The burial of allochthonous particles, derived from external sources such as rivers or tidal influxes, facilitates the formation of stable MAOC through binding to mineral surfaces or occlusion within microaggregates. The proportions of particulate organic C (POC) and MAOC are important predictors for molecular compositions of soil organic matter. Lipid proportions within molecular composition decrease as POC and autochthonous C proportions increase. These findings provide new insights into the coupled control over SOC sequestration in BCEs, emphasizing the role of allochthonous inputs, proportions of carbon pools, and persistent organic components.

A novel ultra-sensitive semiconductor SERS substrate V5S4 nanopompons for the specific detection of antibiotics with AI technology - Weida Zhang; Yusi Peng; Chenglong Lin; Meimei Xu; Shuai Zhao; Dan Li; Yingchun Yang; Yong Yang (Chemical Engineering Journal, 2024)

Copper Promotes LPS-Induced Inflammation via the NF-кB Pathway in Bovine Macrophages - Hongrui Guo; Lin Jing; Chenglong Xia; Yanqiu Zhu; Yue Xie; Xiaoping Ma; Jing Fang; Zhisheng Wang; Zhicai Zuo (Biological Trace Element Research, 2024)

Beach erosion and typhoons reduce green turtle nesting grounds on the Xisha Islands, South China Sea - Ting Zhang; Chenglong Zhang; Yupei Li; Yangfei Yu; Xiaoyu An; Yongkang Jiang; Jichao Wang; Liu Lin; Hai-Tao Shi (Frontiers in Marine Science, 2024)
Introduction Sea turtles are ideal flagship and umbrella species for marine biodiversity conservation. The quality of nesting grounds is crucial for the successful reproduction of sea turtles, as it determines whether they can successfully nest and hatch. The Xisha Islands represent the largest remaining nesting grounds for green turtles in China. However, they face numerous threats and lack management guidelines for nesting ground restoration. Methods In this study, we continuously monitored the beach changes and coastal erosion on North Island, which is located in the northern region of the Xisha Islands, from 2019 to 2022. Results From 2020 to 2022, the beach area on North Island decreased annually by 11,800 m 2 , accounting for 24.39% of the beach area in 2020. The proportion of suitable nesting sand types (including coarse and medium sands) also decreased annually, with a reduction of 40–70% on the southern beach of North Island. The peak nesting period of green turtles on North Island coincides with the frequent occurrence of typhoons in the South China Sea, causing tidal surges that inundate green turtle nests, resulting in an average nest loss rate of 35.25%. Discussion Based on the above threats, it is recommended to promptly initiate habitat restoration in severely eroded areas of green turtle nesting grounds to prevent further declines in nesting area and quality. Additionally, measures such as nest relocation should be implemented to enhance green turtle reproductive success.

Safety analysis code development and validation for lead-cooled fast reactor with helical coiled once-through steam generator - Jiaxin Zhang; Chenglong Wang; Wenxi Tian; G.H Su; Suizheng Qiu; Lin Xian; Kun Cheng; Xiao Chu; Shiying Wei; Guo Chen (Annals of Nuclear Energy, 2024)

Experimental and mechanism study of Ca-based desulfurizer with composite modification for low concentration SO2 removal under low-temperature - Ying Jia; Jingxuan Jiang; Chenglong Wang; Pengxiang Sun; Yong Dong; Lin Cui (Process Safety and Environmental Protection, 2024)

Crustal-mantle layering deposits in the Von Kármán crater, South Pole-Aitken basin - Zhi Zhong; Yuqi Qian; Chenglong Li; Alexander Y. Sun; Zhongxian Cai; Lei Lin; Xu Guo; Yanbin Kuang; Shiqi Wen; Long Xiao (Earth and Planetary Science Letters, 2024)

Machine learning for subsurface geological feature identification from seismic data: Methods, datasets, challenges, and opportunities - Lei Lin; Zhi Zhong; Chenglong Li; Andrew Gorman; Hao Wei; Yanbin Kuang; Shiqi Wen; Zhongxian Cai; Fang Hao (Earth-Science Reviews, 2024)

Accumulation rate and sources of plastic marine litter at nesting grounds of green turtles on the North Island of Qilianyu, Xisha Islands, South China Sea - Ting Zhang; Yongkang Jiang; Deqin Li; Chenglong Zhang; Yunteng Liu; Yupei Li; Yangfei Yu; Jichao Wang; Hai-Tao Shi; Liu Lin (Marine Pollution Bulletin, 2024)

Co-exposure to fluoride and sulfur dioxide induces abnormal enamel mineralization in rats via the FGF9-mediated MAPK signaling pathway - Ying Lv; Jin Yao; Yang Wang; Guohui Bai; Changhu Lin; Chenglong Tu (Environmental Research, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

SeisGAN: Improving Seismic Image Resolution and Reducing Random Noise Using a Generative Adversarial Network - Lei Lin; Zhi Zhong; Chuyang Cai; Chenglong Li; Heng Zhang (Mathematical Geosciences, 2024)

Prevalence and distribution of antibiotic-resistant bacteria in the rhizosphere and rhizoplane of Suaeda salsa and Sporobolus alterniflorus grown in a pristine environment - Yu Wang; Fang Yang; Qianwen Liu; Lin Sun; Weihua Chen; Qingfeng Yu; Chenglong Pan; Guanhong Jiang; Xin'an Jiao; Yunzeng Zhang (Applied Soil Ecology, 2024)

A facile, green strategy to synthesize N/P self-doped, biomass-derived, hierarchical porous carbon from water hyacinth for efficient VOCs adsorption - Chenglong Yu; Junhui Dan; Zewei Liu; Jinliang Wang; Jiayang Wang; Hansun Fang; Fayin Lai; Danping Li; Lin Li; Fengying Li; Chunhuo Zhou; Bichun Huang (Fuel, 2024)

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Ash problems and prevention measures in power plants burning high alkali fuel: Brief review and future perspectives - Pengxiang Sun; Chenglong Wang; Miao Zhang; Lin Cui; Yong Dong (Science of The Total Environment, 2023)

Soil carbon-fixing bacterial communities respond to plant community change in coastal salt marsh wetlands - Qihang Liao; Chao Lu; Feng Yuan; Qinya Fan; Hongyu Chen; Lin Yang; Penghua Qiu; Ziyue Feng; Chenglong Wang; Xinqing Zou (Applied Soil Ecology, 2023)

Transient thermoelectric characteristics of the principle prototype for the heat pipe cooled nuclear Silent themoelectirc reactor (NUSTER) - Kailun Guo; Yin Zhang; Xingyang Lin; Jinlu Huang; Chenglong Wang; Suizheng Qiu; Wenxi Tian; Guanghui Su (Annals of Nuclear Energy, 2023)

Preparation of micro-fibrillated cellulose fibers by a simple two-step refining process for paper- based flexible electronic devices - Chenglong Fu; Changmei Lin; Weipeng Zhang; Yaling Lin; Jinhong Xiu; Yonghao Ni; Liulian Huang (Chemical Engineering Journal, 2023)

Humidity sensitivity reducing of moisture swing adsorbents by hydrophobic carrier doping for CO2 direct air capture - Hao Dong; Tao Wang; Xiaobo Wang; Fengsheng Liu; Chenglong Hou; Zhengfeng Wang; Weishan Liu; Lin Fu; Xiang Gao (Chemical Engineering Journal, 2023)

An Improved YOLOv5s-Based Scheme for Target Detection in a Complex Underwater Environment - Chenglong Hou; Zhiguang Guan; Ziyi Guo; Siqi Zhou; Mingxing Lin (Journal of Marine Science and Engineering, 2023)
At present, sea cucumbers, sea urchins, and other seafood products have become increasingly significant in the seafood aquaculture industry. In traditional fishing operations, divers go underwater for fishing, and the complex underwater environment can cause harm to the divers’ bodies. Therefore, the use of underwater robots for seafood fishing has become a current trend. During the fishing process, underwater fishing robots rely on vision to accurately detect sea cucumbers and sea urchins. In this paper, an algorithm for the target detection of sea cucumbers and sea urchins in complex underwater environments is proposed based on the improved YOLOv5s. The following improvements are mainly carried out in YOLOv5s: (1) To enhance the feature extraction ability of the model, the gnConv-based self-attentive sublayer HorBlock module is proposed to be added to the backbone network. (2) To obtain the optimal hyperparameters of the model for underwater datasets, hyperparameter evolution based on the genetic algorithm is proposed. (3) The underwater dataset is extended using offline data augmentation. The dataset used in the experiment is created in a real underwater environment. The total number of created datasets is 1536, and the training, validation, and test sets are randomly divided according to the ratio of 7:2:1. The divided dataset is input to the improved YOLOv5s network for training. The experiment shows that the mean average precision (mAP) of the algorithm is 94%, and the mAP of the improved YOLOv5s model rises by 4.5% compared to the original YOLOv5s. The detection speed increases by 4.09 ms, which is in the acceptable range compared to the accuracy improvement. Therefore, the improved YOLOv5s has better detection accuracy and speed in complex underwater environments, and can provide theoretical support for the underwater operations of underwater fishing robots.

A new catalyst CHCP-Fe2O3 for enhanced removal of tetracycline through the Fenton-like process: Economical synthesis, catalytic performance, and practicability - Jiao He; Baoyou Pei; Chenglong Deng; Dongha Huang; Bihong Lv; Cheng Peng; Genggeng Luo; JinQing Lin (Journal of Water Process Engineering, 2023)

Sodium Fluoride and Sulfur Dioxide Derivatives Induce TGF-β1-Mediated NBCe1 Downregulation Causing Acid–Base Disorder of LS8 Cells - Ying Lv; Wentai Wang; Lili Yao; Jiaojiao He; Guohui Bai; Changhu Lin; Chenglong Tu (Biological Trace Element Research, 2023)

Optimized Mo-doped IrOx anode for efficient degradation of refractory sulfadiazine - Xiang Shao; Chenglong Ma; Lin Zhu; Chongjie Zou; Limei Cao; Ji Yang (Environmental Science and Pollution Research, 2022)

Determination of cadmium in Chinese pepper and its health implications based on bioaccessibility - Zelan Wang; Jie Yao; Chenglong Tu; Ting Yang; Dali Sun; Changhu Lin (Environmental Science and Pollution Research, 2022)

Ultra-high adsorption of Hg0 using impregnated activated carbon by selenium - Ye Liu; Chenglong Ma; Jiacheng Zhou; Lin Zhu; Limei Cao; Ji Yang (Environmental Science and Pollution Research, 2022)

Protracted formation of nodular cherts in marine platform: new insights from the Middle Permian Chihsian carbonate successions, South China - Chao Liu; Jiao Ma; Lin Zhang; Chenglong Wang; Jiao Liu (Carbonates and Evaporites, 2022)

Fluorine enrichment of vegetables and soil around an abandoned aluminium plant and its risk to human health - Lingling He; Chenglong Tu; Shouyang He; Jiulai Long; Ya Sun; Yan Sun; Changhu Lin (Environmental Geochemistry and Health, 2021)

Nitrogen‐induced acidification, not N‐nutrient, dominates suppressive N effects on arbuscular mycorrhizal fungi - Shang Pan; Yang Wang; Yunpeng Qiu; Dima Chen; Lin Zhang; Chenglong Ye; Hui Guo; Weixing Zhu; Aiqun Chen; Guohua Xu; Yi Zhang; Yongfei Bai; et al. (Global Change Biology, 2020)
Arbuscular mycorrhizal fungi (AMF) form symbiosis with most terrestrial plant roots, obtaining photosynthates in return for mineral nutrients. Ecological theories based on the economics of trading partnership predict that nutrient enrichment would suppress AMF. Experimental results from nitrogen (N) and phosphorus (P) additions, however, were highly variable, and the underlying mechanisms remain unclear. Here we show distinct AMF responses to soil N:P stoichiometry manipulations via gradients of long‐term N and P additions in a Mongolian steppe. A complementary experiment with an acid addition gradient was designed to help tease apart the effect of N‐induced acidification from N nutrient. AMF root colonization and extraradical fungal biomass progressively decreased along the P gradient under two distinct host plant species, suggesting a carbon (C)‐P tradeoff. In contrast, low to moderate N inputs increased both AMF parameters, corresponding to the increasing N:P ratio. Yet, high N inputs reduced AMF colonization and biomass, and the magnitudes of N‐led inhibition were similar to those under acid additions that induced comparable changes in soil pH. Structural equation modeling further showed that while soil N:P stoichiometry primarily controlled the effect of P addition on AMF, N‐induced soil acidity overtook the N:P stoichiometry under high N inputs and dominated the effects of reactive N on AMF. In addition, AMF community composition in roots was more dependent on host plants and unresponsive to changes in soil nutrients. We further proposed a comprehensive framework that integrates biological and geochemical effects of reactive N and P inputs on AMF. Together, these results indicate that while the C‐P tradeoff controls P suppression of AMF, N‐induced acidification dominates the N inhibition. Our findings suggest that incorporation of geochemical impacts of N and P inputs would facilitate modeling efforts to project mycorrhizal impact on plant interactions and soil C balance under future nutrient enrichment scenarios.

Whole-genome mining and in silico analysis of FAD gene family in Brassica juncea - Yufei Xue; Chengyan Chai; Baojun Chen; Xiaofeng Shi; Bitao Wang; Fanrong Mei; Manlin Jiang; Xueli Liao; Xia Yang; Chenglong Yuan; Lin Zhang; Yourong Chai (Journal of Plant Biochemistry and Biotechnology, 2020)

Characterization and Genome Analysis of a Novel Alteromonas Phage JH01 Isolated from the Qingdao Coast of China - Dongxu Wang; Yong Jiang; Shicong Xiao; Min Wang; Qian Liu; Liyang Huang; Chenglong Xue; Qi Wang; Tongtong Lin; Hongbing Shao; Andrew McMinn (Current Microbiology, 2019)

Groove structure of porous hydroxyapatite scaffolds (HAS) modulates immune environment via regulating macrophages and subsequently enhances osteogenesis - Chenglong Li; Lu Yang; Xiaohua Ren; Mu Lin; Xiliang Jiang; Daonan Shen; Taotao Xu; Jing Ren; Lijuan Huang; Wei Qing; Jiajun Zheng; Yandong Mu (JBIC Journal of Biological Inorganic Chemistry, 2019)

Improving arsenic mobility concentration from As-polluted soils by the functional strains - JianFeng Bai; XianGui Lin; Jue Dai; JianFeng Hua; Hua Qin; JunLi Hu; YiMing Wang; ChengLong Zhang; JingWei Wang; WenYi Yuan (Science China Earth Sciences, 2015)

XZH-5 inhibits STAT3 phosphorylation and causes apoptosis in human hepatocellular carcinoma cells - Yan Liu; Aiguo Liu; Zhenghu Xu; Wenying Yu; Hong Wang; Chenglong Li; Jiayuh Lin (Apoptosis, 2011)